The first record of a sauropod dinosaur from Antarctica - Cerda, Ignacio Alejandro; Carabajal, A. Paulina; Salgado, Leonardo; Coria, Rodolfo Anibal; Reguero, Marcelo Alfred; Tambussi, Claudia Patricia; Moly, Juan J. (Naturwissenschaften)
Sauropoda is one of the most diverse and geographically widespread clades of herbivorous dinosaurs, and until now, their remains have now been recovered from all continental landmasses except Antarctica. We report the first record of a sauropod dinosaur from Antarctica, represented by an incomplete caudal vertebra from the Late Cretaceous of James Ross Island. The size and morphology of the specimen allows its identification as a lithostrotian titanosaur. Our finding indicates that advanced titanosaurs achieved a global distribution at least by the Late Cretaceous. © 2011 Springer-Verlag. Fil: Cerda, Ignacio Alejandro. Universidad Nacional de Río Negro. Sede Alto Valle. Instituto de Investigaciones en Paleobiología y Geología; Argentina Fil: Carabajal, A. Paulina. Provincia del Neuquén. Municipalidad de Plaza Huincul. Museo "Carmen Funes"; Argentina Fil: Salgado, Leonardo. Universidad Nacional de Río Negro. Sede Alto Valle. Instituto de Investigaciones en Paleobiología y Geología; Argentina Fil: Coria, Rodolfo Anibal. Universidad Nacional de Río Negro. Sede Alto Valle. Instituto de Investigaciones en Paleobiología y Geología; Argentina Fil: Reguero, Marcelo Alfred. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina Fil: Tambussi, Claudia Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Moly, Juan J. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina